Numerical investigation on the nanofluid flow and heat transfer in a wavy channel - Ahmed M.A.; Yusoff M.Z.; Shuaib N.H. (Springer Verlag, 2023)
In this article, laminar convective heat transfer of copper-water nanofluid in isothermally heated wavy -wall channel is numerically investigated. The governing continuity, momentum and energy equations in body-fitted coordinates are discretized using finite volume approach and solved iteratively using SIMPLE algorithm. The study covers Reynolds number and nanoparticle volume concentration in the ranges of 100800 and 05 % respectively. The effects of nanoparticles volume concentration and Reynolds number on velocity and temperature profiles, the local Nusselt number, the local skin-friction coefficient, average Nusselt number, pumping power and heat transfer enhancement are presented and analyzed. Results show that there is a significant enhancement in heat transfer by addition of nanoparticles. This enhancement increase with concentration of particles but the required pumping power also increases. The present results display a good agreement with the literature. Springer International Publishing Switzerland 2015.